Topography-based customized trans-epithelial phototherapeutic keratectomy for anterior corneal scar removal. Issue 3 (May 2021) - Shetty, Rohit; Shroff, Rushad; Chhabra, Aishwarya; Arora, Ritu; Lalgudi, Vaitheeswaran Ganesan
Purpose: To report a case of management of a post-LASIK superficial corneal scar using a novel single-step topography-based customized phototherapeutic keratectomy (PTK). Methods: Surgical technique description. Results: Ablation was planned using Schwind Amaris ® 1050RS excimer laser as decentered trans-epithelial PTK of 5 mm × 3.5 mm of 75 µm depth exactly over the area of the scar. UDVA, CDVA improved from 20/60 and 20/40 pre-operatively to 20/30 and 20/20p post-operatively. Refractive error improved from −2.5 DC @135 to +0.25 DS/−0.25 DC @75. Regularization of topography and stromal surface on ASOCT was noted with minimal hyperopic shift. Another step of ablation to address induced hyperopia was not required. Conclusion: Topography-based customized PTK appears to be an effective novel technique for the management of superficial corneal scars with minimal induced refractive change. This technique holds promise as an alternative in the targeted management of superficial corneal scars, traditionally treated by conventional PTK, without significant ablation of normal tissue.